(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the use of integrated teaching methods in English classes to increase student engagement and motivation. Based on the theoretical foundations of integrated education, the study provides insight into the implementation of interdisciplinary lessons, discusses practical methods for activating students, and evaluates the results of integrating English with other subjects.